The Rejection of Prophetic Traditions: Analyzing the Inkar Sunnah Movement in West Sumatra, Indonesia - Luqmanul Hakim; Suci Amalia Yasti; Yassinta Ananda (UIN Sunan Kalijaga Yogyakarta, 2024)
This article explores the ideological stance of the Inkar Sunnah movement, which rejects the prophetic traditions (Sunnah) as a source of Islamic law, focusing on its development in West Sumatra, Indonesia. Historically, this movement can be traced back to political and sectarian conflicts in early Islamic history, such as those involving the Khawarij, Shia, and Mu'tazilah sects. Over time, skepticism towards hadith, fueled by fabricated traditions and modern Orientalist critiques, gained traction. Prominent figures like Dalimi Lubis and Nazwar Syamsu have continued to propagate Inkar Sunnah beliefs in modern Indonesia, advocating that the Qur’an alone suffices for Islamic jurisprudence. This research adopts a qualitative library approach, analyzing primary texts by these figures and secondary sources on hadith scholarship. The study critically examines their arguments and the socio-political context that allowed their ideas to proliferate, as well as strategies to counter this ideological challenge within Indonesian Islamic discourse. The findings reveal a persistent tension between traditional Sunni orthodoxy and reformist interpretations that seek to minimize or outright reject the role of the Sunnah, posing significant implications for Islamic legal and theological frameworks.